Building and district administrator perceptions of the Kansas dyslexia initiatives - Dempewolf, Andrew Ryan (Kansas State University, 2023)
The purpose of this qualitative study was to examine building and district administrators’ perceptions of the Kansas Dyslexia Initiatives. Their awareness and experiences may influence how administrators understand, plan for, and align the current approach for reading instruction within their respective buildings or district in relation to the dyslexia requirements. While other studies have documented the perceptions of teachers, principals, parents, and other stakeholders’ understanding of dyslexia, there appeared to be limited research that related specifically to Kansas’ efforts to address dyslexia in the public-school setting. The study aims to answer three research questions. First, what factors impact the extent to which administrators implement and understand the Kansas Dyslexia Initiatives? Second, how do administrators align instructional approaches to reading to adhere to the Kansas Dyslexia Initiatives? The overarching research question for this study explored administrators’ understanding of the Kansas Dyslexia Initiatives. A rural, kindergarten-12th grade Kansas public school district was selected for this study. Five school personnel -- a superintendent, a director of special education, and three building principals -- were first surveyed to identify demographic information of the participants, role in the school system, and years of experience in school/district leadership. Research participants were then interviewed to share their knowledges of the Kansas Dyslexia Initiatives, past and current reading instructional practices, and efforts to adhere to the initiatives. A review of relevant documents provided by the school district was completed. Data analysis utilized Tesch’s (1990) method of data analysis. After interviews were transcribed verbatim data analysis began by reading all transcriptions, making sense of the transcribed data, and listing all of the topics and clustering similar topics together. Then, columns were created with clustered topics. Topics were abbreviated as codes and included next to the appropriate segments. Five themes were discovered during this study: (a) need for quality and effective professional development, (b) time constraints to adhere to the Kansas Dyslexia Initiatives, (c) availability of resources to intervene for students with dyslexia, (d) alignment of curriculum to satisfy necessary instructional changes, and (e) difficulty of change. The study includes descriptive data from surveys, interviews, and review of artifacts that further the knowledge in the field of education related to efforts to assist students with dyslexia. Based on the findings, I identified 15 implications for teaching and learning, administrators, and the Kansas State Department of Education.
Keywords: Dyslexia; Reading instruction; Theoretical orientation to reading; Administrators